Reorienting historic house museums: An anarchists guide - Ryan, Deborah; Vagnone, Franklin (ARCC Conference Repository, 2014)
Although other types of cultural sites are experiencing growth, Historic House Museums (HHMs) are seeing declining visitation, financial instability, and misguided Board stewardship. (Rocco 2013) All too often, HHMs are places where a well-intended docent points at obscure portraits, and gestures into barren rooms while sharing a seemingly fact-based, exclusive narrative about the great deeds of the great, white man who once lived in the home. There are few actual signs of habitation or the complexity of family life, and any opportunity for a shared, meaningful, and human connection across generations disappears in the stark museum atmosphere. Frozen in a pre-determined period of historic interpretation, HHMs fall harshly out of sync with the larger community as demographics change around them. They have become autonomous, self-referential and insular in an era defined by social media, mass communication and the collaborative process. The well-meaning Board and staff leadership of HHMs, with expertise primarily in museum studies, history and collections management, is ill equipped to deal with either the contemporary understanding of context, or the civic engagement expertise of urban designers and architects. The Anarchist Guide for Historic House Museums (AGHHM) attempts to bridge some of those disciplinary boundaries and offers a comprehensive strategy for reorienting HHMs from a curated museum setting to a new paradigm of real-life habitation. This more inclusive re-orientation is organized under four guiding themes of Community, Experience,Habitation and Shelter, and is illustrated as The Anarchist Guide for Historic House Museums Graphic ManifestoThe Historic House Trust of New York City has tested the AGHHM concepts at several of its historic house sites. AGHHM inspired events have been undertaken at NYC's Morris-Jumel Mansion and have led to substantial increases in the number of first-time visitors, press, and funding/earned revenue A follow-up study funded by a $100,000 grant from the New York Community Trust is now underway to design, launch and evaluate an Anarchist Plan for the Latimer House Museum in Queens. The former home of African-American inventor and electrical pioneer Lewis Howard Latimer, the house is located in what has become a Chinese/Korean community, and offers a compelling narrative that has the potential ability to bridge the past and the present, and act as a center of social history, explorative experienceand common identity.